Liposome: A Novel Carrier for Targeting Drug Delivery System - Patel, Vrunda (Asian Journal of Pharmaceutical Research and Development, 2020)
Targeted drug delivery, sometimes called Smart drug delivery is a method of delivering active molecules to the target site by increasing the concentration of active molecules and produces the desired effects without disturbing the bio-environment. This system is based on a technique that delivers precise amount of an active ingredient for a prolonged period of time to a targeted diseased area inside the body. This helps to maintain the specified plasma and tissue drug levels within the body, thereby preventing any harm to the healthy tissue via the drug. It is advantageous in terms of reduction in the frequency of administration, having a more uniform effect of the drug, reduction of side-effects and reduced fluctuation in circulating drug levels. Among several vesicular drug delivery systems, Liposome have attracted a lot of attention than alternative systems because of several meritable features like excellent chemical and biological stability, good solubilization power, promote intracellular delivery of bio-active molecules, reduce the uptake of macrophages and encapsulate each hydrophilic in addition as lipophilic drug molecules. The focus of this review is to discuss liposome with special emphasis on targeting of drugs.